Tectonic Pattern Imaging of Southern Sumatra Region Using Double Difference Seismic Tomography - Akmal Firmansyah; Wandono Wandono; Mohamad Ramdhan (Badan Riset dan Inovasi Nasional, 2022)
Southern Sumatra and its surroundings are close to the contact zone of the Indo-Australian plate and Eurasian plate, so the area always relates to the high seismicity zone. The Sumatran subduction zone, the Mentawai fault, and several segments of the Sumatran fault drive seismic activities in the area. Tectonic settings are essential to understanding the area's source and hazard. This understanding can be obtained using the relocated hypocenter distribution and the 3D velocity model in the area. Relocated hypocenters and velocity models are obtained from simultaneous inversion from the BMKG earthquake catalog in January 2012-December 2020 using the double difference seismic tomography method. Seismic velocity inversion of P- and S- wave tomograms image the thermal zone beneath Dempo and Patah volcanoes at a depth of 30-50 km. Slab dehydration is also observed in several forearc high zone. Both phenomena are associated with negative anomalies. The Sumatran and Mentawai fault zones are marked between negative and positive anomalies on the contact zone. The subducted slab of the Indo-Australian plate is observed until a depth of 150 km, which is the maximum depth of nodes used in this study. The granitic basement beneath Anak Krakatau volcano is detected until 10 km. Two of those geological features are related to positive anomalies.